PENGARUH TIPE BUDAYA ORGANISASI TERHADAP PERILAKU KNOWLEDGE SHARING: PENDEKATAN KONSEP - Hermanto Hermanto (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2018)
Resources are central to the existence of any organisation, and among these resources, knowledge is recognised as one of the most important. Knowledge can be categorised as explicit or tacit. Explicit knowledge can be articulated, stored independently, and easily communicated. Conversely, tacitknowledge is embedded deep in people’s minds and is not easily shared. Attempts to share can be slow, costly, and uncertain. Although it is acknowledged that there are inherent benefits to tacitknowledge,people, generally, are reluctant to share it because of various barriers. According to prior research,organisational culture is one of the main barriers. This paper proposes a conceptual framework that will facilitate the study of the influence of organisational culture types on tacitknowledge-sharing behaviour.Keywords: Organisational Behaviour, Innovation, Knowledge Management